2004
DOI: 10.1002/jgm.564
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological consequences of delivering an adenoviral vector in the rat brain

Abstract: Neuropathological damage in the dopaminergic system, caused by high doses of adenoviral vectors, has not previously been documented. To minimise damage and prolong transgene expression, it is important that the dose of vectors to be delivered is carefully optimised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The functionality of the adenoviral A-CREB-expressing vector was established in a previous study: a CREB-expressing vector but not the A-CREB vector protected cells from excitotoxic and ischemic stress (Glover et al, 2004). Although adenoviral transduction has been used previously in behavioral studies, such as those investigating restoration of motor function in animal models of dopamine depletion (Umegaki et al, 1997;McMenamin et al, 2004), to our knowledge, this is the first time it has been used to demonstrate an interference with recognition memory.…”
Section: Discussionmentioning
confidence: 95%
“…The functionality of the adenoviral A-CREB-expressing vector was established in a previous study: a CREB-expressing vector but not the A-CREB vector protected cells from excitotoxic and ischemic stress (Glover et al, 2004). Although adenoviral transduction has been used previously in behavioral studies, such as those investigating restoration of motor function in animal models of dopamine depletion (Umegaki et al, 1997;McMenamin et al, 2004), to our knowledge, this is the first time it has been used to demonstrate an interference with recognition memory.…”
Section: Discussionmentioning
confidence: 95%
“…adenovirus-mediated gene therapy has been tested as a potential treatment for Parkinson's disease in animal models. It is suggested that the outcome of gene transfection can depend on the physiological state of target cells and tissue [15,16]. It is possible that in the experimental models of PD the success of gene therapy could be affected by the condition of nigrostriatal cells, too.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of sustained ferritin over-expression may be mitigated by the use of adenoviral vectors, which tend to produce transient gene expression [39]. However, any benefit may then be negated by a direct cytotoxic or inflammatory response [40]. Further investigation is needed to determine if ferritin gene transfer is feasible in vivo, and if it also protects neurons and other vulnerable cell populations.…”
Section: Discussionmentioning
confidence: 99%